Essential PTC Mathcad Prime 3.0: a guide for new and current users - Maxfield, Brent (Academic Press, 2014)
Learn how to use PTC® Mathcad Prime® 3.0, one of the world's leading tools for technical computing, in the context of engineering, science, and math applications. Quickly harness the power of PTC Mathcad Prime 3.0 to solve both simple and complex problems. Essential PTC® Mathcad Prime® 3.0 is perfect for college students, first-time users, and experienced Mathcad 15 users who are moving to PTC Mathcad Prime 3.0. Updated from Maxfield's popular Essential Mathcad, this book introduces the most powerful functions and features of the new PTC Mathcad Prime 3.0 software and teaches how to apply them to create comprehensive calculations for any quantitative subject. Examples from several fields demonstrate the power and utility of PTC Mathcad's tools while also demonstrating how users can eff ectively incorporate Microsoft® Excel spreadsheets into the software. Learn the basics faster: Chapter 1 introduces many fundamentals of Mathcad, allowing the reader to begin using the program in less time.Learn PTC Mathcad tools in context: Incorporates many applied examples and problems from a wide variety of disciplines.Thorough discussion of many PTC Mathcad tools: Units, arrays, plotting, solving, symbolic calculations, programming, algebra, calculus, differential equations, reading from files, writing to files, and incorporating MS Excel spreadsheets.Each copy of the book includes a code to download PTC® Mathcad Prime® 3.0 Student Edition, giving the user a full year of use from the time of installation. (The Student Edition software is intended for educational purposes only.)